2018
DOI: 10.1371/journal.pone.0190741
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal force is correlated with cognitive function directly as well as indirectly via food intake in community-dwelling older Japanese: From the SONIC study

Abstract: BackgroundGrowing evidence suggests that oral health may be an important factor associated with cognitive function in aged populations. However, many previous studies on this topic used insensitive oral indicators or did not include certain essential covariates. Thus, we examined the association between occlusal force and cognitive function in a large sample of older adults, controlling for dietary intake, vascular risk factors, inflammatory biomarkers, depression, and genetic factors.MethodsIn this cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 34 publications
2
42
2
Order By: Relevance
“…However, only a limited number of studies have examined the association between cognitive function and oral motor function with risk factors taken into consideration (Ikebe et al, 2018;Watanabe et al, 2018). As such, this study is the first to examine the association between cognitive function and multiple oral motor functions in older people with either normal cognitive function or mild cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a limited number of studies have examined the association between cognitive function and oral motor function with risk factors taken into consideration (Ikebe et al, 2018;Watanabe et al, 2018). As such, this study is the first to examine the association between cognitive function and multiple oral motor functions in older people with either normal cognitive function or mild cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ikebe et al reported that decreased occlusal force might lead to decreased cognitive function (Ikebe et al, 2018). These reports suggested that oral motor function was associated with cognitive function.…”
Section: Introductionmentioning
confidence: 94%
“…To evaluate the influence of rs650439 genotype on plasma klotho concentration, we collected blood samples of 70 ± 1 year-old community-dwelling adults in Japan who participated in the SONIC (Septuagenarians, Octogenarians, Nonagenarians Investigation with Centenarians) study [3036]. Initially, genotypes of rs650439 were determined using the TaqMan SNP genotyping assay (Applied Biosystems Japan, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiologic studies have suggested associations between cognitive ability and oral conditions, such as number of teeth (Luo et al, 2015;Li et al, 2017;Oh et al, 2018) and dental occlusion (Ono et al, 2010;Franco et al, 2012;Takeuchi et al, 2015). Furthermore, occlusal force (Takeshita et al, 2016;Ikebe et al, 2018) and chewing ability have been shown to have effects on cognitive ability (Chen et al, 2015;Natalie et al, 2015;Seraj et al, 2017). Oral reconstruction by means of wearing a denture may induce cortical activation in prefrontal, sensorimotor, and sensory association cortices during chewing performance (Kimoto et al, 2011;Kamiya et al, 2016) and might also contribute to antiaging cognitive activation in the prefrontal cortex of elderly edentulous patients (Banu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%